Differences in Neuritogenic Activity and Signaling Activation of Madecassoside, Asiaticoside, and Their Aglycones in Neuro-2a cells - Nalinratana, Nonthaneth; Meksuriyen, Duangdeun; Ongpipattanakul, Boonsri (Planta Medica, 2018)
Madecassoside (MS) and asiaticoside (AS) along with their aglycones, madecassic acid (MA) and asiatic acid (AA), are considered the major neuroactive triterpenoid constituents of Centella asiatica. In this study, we aimed to compare MS, AS, MA, and AA for their neurite outgrowth activities and mechanisms in Neuro-2a cells. Immunofluorescent cell staining showed MS and AS significantly increased the percentage of neurite-bearing cells (%NBC) and the neurite length with higher potency than MA and AA. The triterpenoid glycosides induced sustained extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) phosphorylation, while their aglycones activated only transient signaling of ERK1/2. Suppression of ERK1/2 activation significantly abolished not only cAMP response element-binding protein (CREB) phosphorylation but also the increment of %NBC and neurite length in MS- and AS-treated cells. Inhibition of ERK phosphorylation did not produce similar blockage of CREB activation and neurite outgrowth in MA- and AA-treated cells. On the other hand, inactivation of protein kinase B (Akt) resulted in a suppression of neurite lengthening in all studied triterpenoids. This is the first study discerning the different signaling pathways of neurite outgrowth activity induced by C. asiatica triterpenoid glycosides and aglycones. Neurite outgrowth activity of the glycosides MS and AS was found to involve the activation of sustained ERK phosphorylation leading to CREB activation, while ERK activation was not associated with MA- and AA-induced neurite outgrowth. In addition, Akt activation was evident to be more involved in neurite elongation process.
Keywords: madecassoside; asiaticoside; madecassic acid; asiatic acid; neurite outgrowth; sustained ERK phosphorylation; Centella asiatica; Apiaceae